Intra-Regional Regional Wage Inequality In Portugal: A Quantile Based Decomposition Analisys - Jo\~ao Pereira; Aurora Galego (European Regional Science Association (ERSA), 2013)
Studies report that economic inequality remained relatively stable since the second world war until the 1980s (Lemieux, 2008). However, in the 1980s and 1990s several studies reveal an upward trend in inequality in many countries (Lemieux, 2008). The vast majority of studies analyse inequality at national level or perform comparisons among countries. Studies focusing on intra-regional inequalities are very scarce. A few examples are Dickey (2007) and Monastiriotis (2000) for England. However, in order to better understand the causes of inequality it is important not only to investigate inequalities at national level and even inter-regional differences, but also to study intra-regional inequality. This paper aims at further investigate inequality by focusing on wage differences within regions. We consider the case of Portugal which is referred as one of the countries with highest economic inequality (OECD, 2005, Cardoso,1998). In particular, we analyse the evolution of intra-regional wage inequality in Portugal between 1995 and 2005 and consider data from Quadros de Pessoal. We employ a quantile-based decomposition method suggested by Melly (2005). To the best of our knowledge, this is the first application of this methodology to the issue of regional wage inequality. This approach has several advantages in relation to the usual index measures commonly used in economic inequality analysis. First, it allows analysing economic inequality along the entire wage distribution. Second, single index measures can yield different rankings of inequality, as they weight differently different parts of the wage distribution. Finally, Melly (2005) method decomposes changes in inequality into components explained by changes of characteristics, returns to characteristics and residuals, allowing an improved knowledge of the causes for changes in inequality. Our results show that wage inequality evolution has been different for the several regions in Portugal. In fact, while inequality at national level slightly decreased between 1995 and 2005, some regions have not followed this evolution. Furthermore, there is as well heterogeneity on the determinants of the wage inequality evolution among the regions. References Cardoso, A (1998), Earnings inequality in Portugal: high and rising?, Review of Income and Wealth, 44(3), 325-343. Dickey, H (2007), â??Regional earnings inequality in Great Britain: evidence from quantile regressionsâ?, Journal of Regional Science, 47(4), 2007, 775â??806. Lemieux, T (2008), â??The changing nature of wage inequalityâ?, Journal of Population Economics, 21, 21-48. Melly, B (2005), â??Decomposition of differences in distribution using quantile regressionâ?, Labour Economics, 12, 577â??590. Monastiriotis, V (2000), Inter and Intra-regional wage inequalities in the UK: sources and evolution, http://www2.lse.ac.uk/geographyAndEnvironment/research/Researchpapers/rp70.pdf OECD (2005), OECD Employment Outlook.
Keywords: J31; J38; C21; 330; Economic inequality; quantile decomposition; regional inequality